Absorption loss and Kerr nonlinearity in barium titanate waveguides - Annina Riedhauser; Charles Möhl; Johannes Schading; Daniele Caimi; David I. Indolese; Thomas M. Karg; Paul Seidler (APL Photonics)
Because of its exceptionally large Pockels coefficient, barium titanate (BaTiO3) is a promising material for various photonic applications at both room and cryogenic temperatures, including electro-optic modulation, frequency comb generation, and microwave-optical transduction. These applications rely on devices with low optical loss to achieve high efficiency. Material absorption sets a lower limit to optical loss and is thus a crucial property to determine, particularly for integrated photonic devices. Using cavity-enhanced photothermal spectroscopy, we measure the absorption loss of BaTiO3 ridge waveguides at wavelengths near 1550 nm to be αabs = 10.9−0.4+5.8 dB m−1, well below the propagation losses due to other sources, such as scattering. We simultaneously determine that the BaTiO3 has a large Kerr nonlinear refractive index of n2,BaTiO3 = 1.8−0.3+0.3 × 10−18 m2 W−1. Considering these results, photonic integrated circuits utilizing BaTiO3 have the potential to achieve significantly higher efficiency than demonstrated to date and are especially interesting for applications exploiting the combination of Pockels and Kerr effects.